Effects of distribution of bone cement on clinical efficacy and secondary fracture after percutaneous kyphoplasty for osteoporotic vertebral compression fractures - Pan, Zejun; Zhou, Quan; Yang, Ming; Deng, Lei; Hu, Xiayu; Lv, Nanning; Yang, Shaofeng; Yang, Huilin (Frontiers in Surgery, 2023)
[Abstract]: Objective: To investigate the effect of bilateral bone cement distribution on the clinical efficacy of percutaneous kyphoplasty (PKP) in the treatment of osteoporotic vertebral compression fracture (OVCF). Methods: According to strict inclusion and exclusion criteria, 109 cases of OVCF patients treated with bipedicular PKP were included in this study from August 2018 to July 2020. According to the distribution morphology of bilateral bone cement in vertebral body, patients were divided into 3 groups, including Group A (n=44): bilateral diffuse type; Group B (n=31): bilateral dense type; Group C (n=34): mixed type. To assess the clinical and radiographic efficacy of the surgery, the visual analogue scale (VAS) score, Oswestry disability index (ODI) score, anterior vertebral height (AVH), anterior vertebral height ratio (AVHR) and local kyphotic angle (LKA) were recorded at preoperatively, 2 days after surgery and 1 year after surgery. Results: Compared with the preoperative recorded value, the VAS score, ODI score, AVH, AVHR and LKA of the three groups were significantly improved at 2 days after surgery and 1 year after surgery (p< 0.05). At 1 year after surgery, the VAS score of Group A was better than that of groups B and C (p< 0.05), and there were significantly differences in ODI score, AVH, and LKA between Group A and Group B (p<0.05). Compared with other bone cement distribution patterns, the incidence of recompression in bilateral diffuse bone cement distribution pattern was lower (p< 0.05). Conclusion: In the mid-term follow-up of patients undergoing bipedicular PKP, diffuse and symmetrical distribution of bone cement can obtain better clinical improvement and lower the incidence of secondary compression.